MECHANICAL TESTING OF HETEROGENEOUS ENERGY COMPONENTS - Pavlin Tadej (Journal of Energy Technology, 2024)
Welding of a high-strength low-alloyed (HSLA) steel with the aim to produce an under-matched weld joint presents a technological challenge for modern welded structure production. Attention should be paid to the level of strength mismatching, which should provide sufficient toughness of the weld metal by using an appropriate welding consumable (wire, electrode) and welding procedure. High toughness of weld metal is necessary to enable local plastic deformation and to prevent brittle fracture. It is of utmost importance to exclude the possibility of plane faults (hydrogen cracking, lack of fusion, etc.) and local-brittle-zone (LBZ) appearance in HSLA steel under-matched welded joints, which can cause failure. This research aimed to estimate the weld metal Crack Tip Opening Displacement (CTOD) fracture toughness using standard procedures for three differently under-matched welded joints.